PENGARUH KONSELING GIZI TERHADAP TINGKAT PENGETAHUAN GIZI, ASUPAN NATRIUM, KALIUM DAN TEKANAN DARAH PASIEN HIPERTENSI - Juenita Elfunam Mado; Maya Kumalasari Sugiyanto; Sanya Anda Lusiana; Sri Iriyanti; Dorci Nuburi (Bajang Institute, 2026)
Nutrition counseling is a nutritional care in the form of an individual approach form of nutritional education to help individuals solve nutritional problems faced. The purpose of this study was to determine the effect of nutritional counseling on the level of nutritional knowledge, sodium intake, potassium and blood pressure of hypertensive patients. This research is an Pre experimental study, using One group pretest and post test design, with a sample of 35 people who meet the inclusion criteria. The data were collected through interviews using questionnaires to determine the nutritional knowledge of respondents and for sodium and potassium intake using recall form 1x24 hours, and blood pressure obtained from examination using tensimeter. Univariate analysis was done descriptively and bivariate analysis using Paired-Samples T Test with α = 0,05 . The results showed that there is a change in the level of knowledge in 35 respondents with the average value before nutrition counseling 44.15% and after nutrition counseling that is 79.43%. There was a change of respondent's intake before nutrition counseling, the average sodium intake of 1398.5 mg daily to 840.25 mg daily after nutrition counseling, average potassium intake of 1697.8 mg per day and after counseling to 2195.0 mg. This is also the same as the respondent's blood pressure, before the average nutrition counseling of the systolic pressure of 151.7 mmHg and diastolic pressure 129,43 mmHg, after the nutrition counseling a mean systolic preasure 92,29 mmHg and diastolic pressure 85,00 mmHg. The result of statistical test shows that the value of p = 0.00 (p <0.05) means that there is influence of nutrition counseling to the level of knowledge, sodium intake, potassium and blood pressure of hypertension patient in work area of ​Puskesmas ​Matani Tomohon Tengah.